PENGARUH PENGGUNAAN METODE ROLE PLAYING TERHADAP HASIL BELAJAR PKN PADA MATERI MENGHARGAI KEPUTUSAN BERSAMA DI KELAS V SEKOLAH DASAR - Dabukke, Barita Esman; Silalahi, Taruli Marito; Hutagaol, Robinson; Irhamna, Nurul Fitria (Universitas Negeri Medan, 2023)
The purpose of this study is to determine the effect of Role Playing method on civics learning outcomes in respect decisions of fifth grade students at SDN 101738 Diski, Sunggal District. This study is quantitative experiment. The population of this study were all fifth grade students at SDN 101738 Diski. The data collection techniques used were tests and observations. The data were analyzed using t-test (One Sample t-test Method). In the implementation of using Role Playing method, students collaborate to play their respective roles. After that, each group will present their conclusions. Student learning outcomes after using Role Playing method obtained an average value of 77.97. Based on the results of the t-test where t-count > t-table = 5.57 > 1.6 with a significant level of 0.05 which states that Ha is accepted and Ho is rejected. So it can be concluded that the use of Role Playing method affect the learning outcomes of civics in respect decisions of fourth grade students at SDN 101738 Diski, Sunggal District.